(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Toni Morrison’s Beloved is a novel about motherhood and mothering. Specifically, it is an interesting story about a slave woman as a mother. The events of the novel are set in the first half of the nineteenth century when the slave population in the United States has increased significantly. It also narrates the fortunes and misfortunes of Sethe, an African slave confined to a plantation in Kentucky named Sweet Home. The owners of the plantation were a childless couple named the Garners. Sethe, unlike most African slave women, had a measure of control over her future on this plantation. She had the option of selecting one of the five slave men on this plantation as her husband and the good fortune of bearing his four children and planning the future for herself and her family, options that few other slaves possessed. Because of her owners and their relatively compassionate views toward their slaves, Sethe, a courageous and daring woman, dared to imagine a future in which her children could escape the bondage of slavery.